2023
DOI: 10.3390/ijms24076388
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Computer-Assisted Analysis of PRAME Immunoreactivity in Dysplastic Nevi and Superficial Spreading Melanomas

Abstract: PRAME (PReferentially expressed Antigen in MElanoma) is a cancer testis antigen that is frequently expressed in melanoma compared to benign melanocytic proliferations and nevi. However, the interpretation of the intensity and distribution of PRAME immunostaining is not standardized a lot, which makes interpretation difficult. PRAME-stained histological slides of superficial spreading melanomas (SSM) and dysplastic nevi (DN) were digitized and analyzed using the digital pathology and image platform QuPath. t-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…According to our data, epidermal expression has a higher significance in the context of the classification of melanocytic lesions. This has also been observed for other immunohistochemical markers [6,26]. Thus, intraepidermal melanocytes-considering subcorneal keratinocytes having a modest 5-hmC expression-should especially be carefully analyzed for 5-hmC expression to facilitate melanoma diagnosis in addition to morphologic features and potentially further immunohistochemical markers.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…According to our data, epidermal expression has a higher significance in the context of the classification of melanocytic lesions. This has also been observed for other immunohistochemical markers [6,26]. Thus, intraepidermal melanocytes-considering subcorneal keratinocytes having a modest 5-hmC expression-should especially be carefully analyzed for 5-hmC expression to facilitate melanoma diagnosis in addition to morphologic features and potentially further immunohistochemical markers.…”
Section: Discussionmentioning
confidence: 73%
“…However, the performance of ROCAUC < 0.8 (epidermal ROCAUC = 0.79, entire lesion ROCAUC = 0.76) lacks diagnostic accuracy compared to other markers such as PRAME. We evaluated PRAME in DN and SSM and presented ROCAUC values of >0.87 [6]. According to this data, we suggested that a high PRAME expression of more than 100 cells/mm 2 is a strong indicator for melanoma, with a specificity of >87%, which is in comparison more reliable than 5-hmC [6].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The specific scoring criteria are detailed in Supplementary Table 2. The scoring criteria were established based on image descriptions from the selected textbook and a literature review on dermatopathology and dermoscopy images [25][26][27][28][29][30][31][32][33][34][35][36][37] . Two highly experienced dermatology experts with over 10 years of practice have reviewed and revised the scoring criteria.…”
Section: Establishment Of Evaluation Criteriamentioning
confidence: 99%